Whole Genome Sequencing and Comparative Genomics Analyses of Pandoraea sp. XY-2, a New Species Capable of Biodegrade Tetracycline - Wu, Xueling; Wu, Xiaoyan; Shen, Li; Li, Jiaokun; Yu, Runlan; Liu, Yuandong; Qiu, Guanzhou; Zeng, Weimin (Frontiers in Microbiology, 2019)
Few bacteria are resistant to tetracycline and can even biodegrade tetracycline in the environment. In this study, we isolated a bacterium Pandoraea sp. XY-2, which could biodegrade 74% tetracycline at pH 7.0 and 30°C within 6 days. Thereafter, we determined the whole genome sequence of Pandoraea sp. XY-2 genome is a single circular chromosome of 5.06 Mb in size. Genomic annotation showed that two AA6 family members-encoding genes and nine glutathione S-transferase (GSTs)-encoding genes could be relevant to tetracycline biodegradation. In addition, the average nucleotide identities (ANI) analysis between the genomes of Pandoraea sp. XY-2 and other Pandoraea spp. revealed that Pandoraea sp. XY-2 belongs to a new species. Moreover, comparative genome analysis of 36 Pandoraea strains identified the pan and specific genes, numerous single nucleotide polymorphisms (SNPs), insertions, and deletion variations (InDels) and different syntenial relationships in the genome of Pandoraea sp. XY-2. Finally, the evolution and the origin analysis of genes related to tetracycline resistance revealed that the six tetA(48) genes and two specific genes tetG and tetR in Pandoraea sp. XY-2 were acquired by horizontal gene transfer (HGT) events from sources related to Paraburkholderia, Burkholderia, Caballeronia, Salmonella, Vibrio, Proteobacteria, Pseudomonas, Acinetobacter, Flavimaricola and some unidentified sources. As a new spicies, Pandoraea sp. XY-2 will be an excellent resource for the bioremediation of tetracycline-contaminated environment.